I spy Christmas : a book of picture riddles - Wick, Walter; Marzollo, Jean. (New York : Cartwheel Books, 1992)
Rhymes invite the reader to find hidden objects in photographs of Christmas items.
Keywords: Picture puzzles -- Juvenile literature; Christmas -- Juvenile literature; Picture puzzles; Christmas -- Miscellanea